Effects of training podiatrists to use imagery‐based motivational interviewing when treating people with diabetes‐related foot disease: a mixed‐methods pilot study - Tracey Kaczmarek; Jaap J. Van Netten; Peter A. Lazzarini; David Kavanagh (Journal of Foot and Ankle Research, 2021)
Abstract Background Self‐care in diabetes related foot disease (DFD) is challenging and contributes to poor outcomes. Motivational Interviewing (MI) can engage people in self‐care and modifying it by integrating imagery may further improve its outcomes. No previous studies have trained podiatrists in using MI to address DFD self‐care. This was the first study on training podiatrists to conduct imagery‐based motivational interviewing (MI) when treating people with DFD, and to examine impacts on MI related skills, job satisfaction and subjective experiences in a mixed‐methods pilot study. Methods Eleven recruited podiatrists (median age: 35 years, 9 female and 2 male) received two 4‐h training sessions, and three received subsequent mentoring. MI and imagery skills were rated using validated tools during two clinical sessions per participant at baseline, and 2‐ and 12‐weeks post‐training. Job satisfaction was assessed at baseline and 12 weeks. Semi‐structured interviews at 12 weeks were analysed using the framework approach. Results Significant improvements over time (p = .006–.044) with substantial effect sizes (η2 = .50–.67) were found in three of four global MI related communication skills and two of four MI behaviours. However, effects on these indices were not sustained to 12 weeks, and imagery was rarely used. Job satisfaction was high at baseline and unchanged at follow‐up (p = 0.34, η2 = .100). In qualitative interviews, MI training and skills were valued, but significant challenges in using MI when treating people with DFD were reported. Conclusion Training podiatrists in MI may have potential but more training, observation and mentoring appear needed to obtain sustained communication changes in practice.